A Review on Mutual Authentication and Location Privacy in Mobile Cloud Computing - Rana, Karuna; Yadav, Himanshu; Agrawal, Chetan (International Journal of Computer Sciences and Engineering, 2019)
In this paper we have explained about the mobile computing features, limitations which are necessarily should know to us for the future enhancements over the services which are provided by the Cloud Servers (CS). A mobile computing is basically a combination of the cloud computing and the mobile devices whose combination provides us the services over cloud which includes: data storage, data security. Also in this paper our aim is to provide a robust anonymous mutual authentication schemes to provide the effective and the secure data access services to its users. The scheme which used will be helpful to replay attackers and will support creation, modification, to read the information which is put away in the cloud servers. This paper likewise addresses client renouncement. Besides, our verification and access control plot is decentralized and hearty, not at all like different access control plans intended for mists which are incorporated. The correspondence, calculation, and capacity overheads are practically identical to incorporated approaches.